Lymphangioma of cheek region–an unusual presentation - Siddharth Gupta; Puneet Ahuja; Usha Rehani; Vishal Singh (Journal of Oral Biology and Craniofacial Research)
ABSTRACT: Background and Objectives: Lymphangiomas are benign hamartomatous tumors of the lymphatic vessels. A lymphatic malformation is a congenital defect that occurs during early embryonic development when the lymphatic vessels do not properly form. The vessels may become blocked and enlarged as lymphatic fluid collects in the vessels, forming a mass or a cyst. About 50% of all lesions are noted at birth and around 90% develop by 2 years of age. Materials and Methods: We report the case of lymphangioma, with an unusual presentation in the cheek region resulting into vestibular obliteration and expanding to the left maxilla diagnosed on the basis of histopathology. The review of literature concerning the clinical and histological features as well as the proper management concerning this hamartomatous entity is included. Results and Conclusion: The various treatment modalities for lymphangioma are surgical excision, radiation therapy cryotherapy, electrocautery, sclerotherapy, steroid administration, embolization, ligation, laser surgery with Nd-YAG and CO2 and radiofrequency tissue ablation technique. An early diagnosis and intervention helps in reducing the functional, psychological disturbances and cosmetic disfigurement.